Losses in a piezoelectric ceramic in high fields - M. SZALEWSKI (Archives of Acoustics)
The paper concerns the problem of measurements of electrical and mechanical losses in a piezoelectric ceramic driven by high electric field and vibrating with high vibration velocity. Deformations and discontinuities of resonance curves appear in this range of the fields. Therefore the application of typical methods of measurements of quality factors is difficult or even impossible. The author proposes to apply the measurements of voltage ratios in a piezoelectric transformer instead of the measurements of resonator quality factors. In the paper the relations connecting the voltage ratios in the piezoelectric transformer with the values of electrical and mechanical losses as well as experimental results are presented. The formulae have been derived using the KLM equivalent circuit for two limits of the transformer load resistance. The obtained results are compared with the results obtained using one of the earlier known measurement method in the range of its applicability.